Exosomes: their role and therapeutic potential in overcoming drug resistance of gastrointestinal cancers - Liu, Jiulian; Gao, Shanyu; Liu, Xiaoming; Dong, Jiaxin; Zhen, Dingwei; Liu, Tong (Frontiers in Oncology, 2025)
Gastrointestinal cancers are prevalent malignant neoplasms in clinical medicine. The development of drug resistance in gastrointestinal cancers result in tumor recurrence and metastasis and greatly diminish the efficacy of treatment. Exosomes, as the shuttle of intercellular molecular cargoes in tumor micro-environment, secreted from tumor and stromal cells mediate drug resistance by regulating epithelial-mesenchymal transition, drug efflux, stem-like phenotype and cell metabolism. Meanwhile, exosomes have already received tremendous attention in biomedical study as potential drug resistant biomarkers as well as treatment strategy in gastrointestinal cancers. Primary challenge to implement this potential is the ability to obtain high-grade exosomes efficiently; however, exosomes lack standard protocols for their processing and characterization. Furthermore, this field suffers from insufficient standardized reference materials and workflow for purification, detection and analysis of exosomes with defined biological properties. This review summarize the unique biogenesis, composition and novel detection methods of exosomes and informed the underlying correlation between exosomes and drug resistance of gastrointestinal cancers. Moreover, the clinical applications of exosomes are also summarized, might providing novel therapy for the individual treatment of gastrointestinal cancers.